The Teacher’s Challenge in 21st Century: Physics and Science Teachers’ ICT Competencies in Learning Process - Elisa Elisa; Fitria Herliana; Ahmad Farhan; Syamsul Rizal (Postgraduate, University of Mataram, 2023)
This study aims to determine the competence of Information and Communication Technology (ICT) of science and physics teachers in Aceh Tamiang District in the learning process. The survey method was used in this study and data to measure teachers' ICT competencies were obtained with a questionnaire instrument. The questionnaire were developed from ICT competences indicators as many as 19 items. The respondents were 40 science and physics teachers in Aceh Tamiang. Data were analyzed using quantitative descriptive analysis and correlation test. Based on the perceptions obtained from the research questionnaire data, the teachers' ICT competence is very high category. In terms of employment status, the average ICT competence of non-civil servant teachers is higher than civil servant teachers. Likewise, from the review of tenure, teachers who have <5 years of service have higher ICT competencies compared to teachers who have 6-15 years and >15 years of service. The correlation test results obtained a weak relationship between employment status and tenure of science and physics teachers in Aceh Tamiang on ICT competence. These results can be a concern for civil servant teachers and teachers who have a longer tenure can further improve ICT competencies in learning to produce quality graduates